Composite particles with non-porous organic-inorganic hybrid material
By using surface porous composite particles of non-porous polymer cores with modified surfaces and non-porous organic-inorganic hybrid materials in the chromatographic stationary phase, the problem of unstable existing chromatographic stationary phases under high pH conditions is solved, and a more stable chromatographic separation effect is achieved.
Patent Information
- Application Number
- CN202380061254.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-02-24
- Publication Date
- 2025-04-01
AI Technical Summary
The existing chromatographic stationary phase is unstable under high pH conditions, resulting in the dissolution of silica nuclear, affecting the long-term stability and efficiency of chromatographic separation.
Using surface porous composite particles of non-porous polymer cores with modified surfaces and non-porous organic-inorganic hybrid materials, a stable porous shell structure is formed by depositing porous inorganic material outside the non-porous polymer core to reduce or eliminate dissolution of the silica core.
Maintain the stability of the chromatographic material under long-term high pH conditions, extend retention time, improve peak shape and improve separation efficiency of analytes.
Smart Images

Figure CN119744197A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of U.S. Provisional Application Serial No. 63 / 401,555, filed on August 26, 2022, entitled “Core-Shell Particles with Non-Porous Hybrid Organic-Inorganic Layer”, which is incorporated herein by reference in its entirety. Technical Field
[0003] The present technology relates to chromatographic materials. More specifically, the present technology relates to superficially porous composite particles for chromatographic separation. Generally speaking, the superficially porous composite particles include a non-porous polymer core, a non-porous organic-inorganic hybrid material in contact with the core, and a porous inorganic material in contact with the non-porous organic-inorganic hybrid material. Background Art
[0004] Chromatography is a separation method involving two phases, one being the stationary phase and the other being the mobile phase. Typically, the stationary phase is porous or non-porous particles packed into a column. The mobile phase flows through the packed column. The sample or analyte to be separated is injected at the beginning of the column and is transported through the system by the mobile phase. As they pass through the column, the different components of the sample are distributed according to their relative affinities for the two phases. The results of the chromatographic separation are then depicted via a chromatogram, where the sample components can be identified by the various peaks or patterns in the chromatogram.
[0005] Measuring the degree of separation between two components is often referred to as the resolution of each component. Resolution can be determined by the efficiency, selectivity, and retention of the separation process. Efficiency refers to the quality of separation of the sample components and is usually determined by the number of separable peaks in the chromatogram. Selectivity refers to the ability of the chromatography to separate the sample components and is usually measured by the retention ratio of the two peaks in question in the chromatogram and can be visualized as the distance between the apexes of the two peaks. Retention or retention time refers to the time it takes for a sample to pass through the chromatographic column and is usually measured as the time interval between the injection of the sample and the detection of its components on the chromatogram.
[0006] Adjusting the mobile phase pH is a powerful tool to improve the retention and selectivity of analytes, especially ionizable analytes, in chromatographic separations. In reversed-phase chromatographic separations of basic compounds, peptides, and biological samples, high pH mobile phases combined with high temperatures are often used to obtain extended retention, excellent peak shape, and good efficiency. Silica-based stationary phases have been preferred in the past due to their stability at neutral pH and high temperatures. However, a common disadvantage is that silica-based stationary phases are unstable at high pH due to dissolution-induced particle corrosion, which in turn limits its use in these applications. An alternative to silica-based stationary phases is to use polymer-based stationary materials. Polymer-based stationary particles have shown some promise, but also have some limitations in column efficiency, especially in the separation of small molecules.
[0007] Superficially porous particles (also known as solid core or core-shell particles) have become popular chromatographic stationary phases due to their improved efficiency and reduced back pressure compared to completely porous particles. Superficially porous particles suitable for chromatographic applications comprise a nonporous core of silica with a porous shell. To date, hybrid technologies on inorganic materials have allowed use under high pH conditions, however these particles continue to exhibit weaknesses due to the dissolution of the nonporous silica core over time. For example, superficially porous particles with organic-inorganic hybrid coatings and / or tightly bound materials have improved high pH stability, however due to prolonged exposure to high pH in a packed column, the particles experience dissolution of the solid silica core, which can lead to column failure. Therefore, there is a need for superficially porous particles with organic-inorganic hybrid coatings for stationary phases that have the ability to remain stable at high pH for extended periods of time. Summary of the invention
[0008] The present technology relates to superficially porous composite particles for chromatographic separations. In particular, embodiments of the present technology relate to reducing and / or eliminating silica core dissolution in the composite particles of the present disclosure.
[0009] The technology disclosed herein relates to surface porous composite particles for chromatographic separation (e.g., stationary phase). The surface porous composite particles of the present technology include a non-porous internal part and a porous part outside the non-porous internal part. In an embodiment, the composite particles include a non-porous polymer core with a modified surface. Non-porous organic-inorganic hybrid materials are deposited or formed on the modified surface of the non-porous polymer core. In order to provide porosity, the porous inorganic material is contacted with the non-porous organic-inorganic hybrid material. The embodiment of the surface porous composite particles of the present technology can be additionally characterized by a bonding material. As a result of using such composite particles in chromatographic separation, the non-porous polymer core of the particles can remain stable at high pH for a long time.
[0010] In one aspect, the present technology is directed to a composite particle comprising a nonporous polymer particle core having a modified surface, a nonporous organic-inorganic hybrid material in contact with the modified surface, and a porous inorganic material in contact with the nonporous organic-inorganic hybrid material.
[0011] The above aspects may include one or more of the following features. In some embodiments, the nonporous polymer particle core of the composite particles is made of a monomer that can be free radically polymerized. In some embodiments, the nonporous polymer particle core is made of styrene, divinylbenzene, methacrylate or acrylonitrile. In some embodiments, the nonporous polymer particle core is made of one or more monomers containing at least two functional groups. In some embodiments, the nonporous polymer particles are made by condensation of monomers. In some embodiments, the monomer is a carboxylic acid / alcohol or a carboxylic acid / amine. In some embodiments, the nonporous polymer particle core is made of one or more monomers that can be polymerized by ring-opening polymerization. In some embodiments, the monomer is an epoxide. In some embodiments, at least a portion of the modified surface of the nonporous polymer particle core includes at least a functional group that is covalently bonded to a nonporous organic-inorganic hybrid coating to form a functionalized surface. In some embodiments, the functional group is at least one of an organic silane characterized by C-Si, an organic titanium characterized by C-Ti, and an organic zirconium characterized by a C-Zr bond. In some embodiments, at least a portion of the modified surface of the nonporous polymer particle core includes at least a functional group that electrostatically interacts with the nonporous organic-inorganic hybrid coating to form a functionalized surface. In some embodiments, the functional group is an amide.
[0012] In some embodiments, the nonporous organic-inorganic hybrid material of the composite particles has a thickness in the range of about 10nm to about 200nm. In some embodiments, the nonporous organic-inorganic hybrid material has a thickness in the range of about 25nm to about 100nm. In some embodiments, the nonporous organic-inorganic hybrid material has a pore volume less than 0.1cc / g (e.g., 0.05cc / g). In some embodiments, the nonporous organic-inorganic hybrid material includes at least one of silicon dioxide, aluminum oxide, titanium, cerium, zirconium, zirconium oxide or ceramic material. In some embodiments, the nonporous organic-inorganic hybrid material includes an organic-inorganic hybrid material based on silicon.
[0013] In another aspect, the present technology relates to a composite particle comprising a nonporous polymer particle core having a modified surface, a nonporous organic-inorganic hybrid material in contact with the modified surface, a porous inorganic material in contact with the nonporous organic-inorganic hybrid material, and a bonding material in contact with the nonporous organic-inorganic hybrid material.
[0014] The above aspects may include one or more of the following features. In some embodiments, the bonding material of the composite particles is incorporated into the non-porous organic-inorganic hybrid material. In some embodiments, the bonding material is also deposited on the outer surface of the composite particles. In some embodiments, the bonding material is also in contact with the modified surface. In some embodiments, the bonding material is incorporated into the modified surface, deposited on the modified surface, or a combination thereof.
[0015] On the other hand, the present technology relates to a composite particle, which includes a nonporous polymer particle core having a modified surface, a nonporous organic-inorganic hybrid material in contact with the modified surface, and the nonporous organic-inorganic hybrid material is deposited on the outermost surface of the porous inorganic material to form a nonporous organic-inorganic hybrid barrier layer on the porous inorganic material outside the composite particle.
[0016] The above aspects may include one or more of the following features. In some embodiments, the composite particles may further include a bonding material. In some embodiments, the bonding material is in contact with at least a portion of the nonporous organic-inorganic hybrid material. In some embodiments, the bonding material is in contact with the nonporous organic-inorganic hybrid barrier layer. In some embodiments, the nonporous polymer particle core is made of one or more of styrene, divinylbenzene, methacrylate or acrylonitrile. In some embodiments, the modified surface is a silyl-modified surface. In some embodiments, the porous inorganic material includes silicon dioxide. In some embodiments, the nonporous organic-inorganic hybrid material includes a silicon-based organic-inorganic hybrid material.
[0017] The present technology provides many advantages over current chromatographic separation means. For example, the use of surface porous composite particles described herein can alleviate core dissolution (i.e., silica core dissolution) in chromatographic applications. That is, surface porous particles with non-porous cores with modified surfaces (e.g., silyl-modified surfaces), non-porous organic-inorganic hybrid materials in contact with the modified surfaces, and porous inorganic shell materials in contact with non-porous organic-inorganic hybrid materials can provide more stable chromatographic materials than the means currently used in the industry (i.e., core-shell particles with silica cores). The present technology can remain stable when exposed to high pH for a long time. Therefore, chromatographic separation using composite particles described herein can result in extended retention, better peak shape, and more effective analyte separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018]
[0011] The foregoing features and advantages and other features and advantages provided by the present technology will be fully understood from the following description of exemplary embodiments when read in conjunction with the accompanying drawings.
[0019] Those skilled in the art will appreciate that the drawings are primarily for illustrative purposes and are not intended to limit the scope of the inventive subject matter described herein. The drawings are not necessarily drawn to scale; in some cases, various aspects of the inventive subject matter disclosed herein may be exaggerated or enlarged in the drawings to facilitate understanding of different features. In the drawings, the same reference numerals generally represent the same features (e.g., functionally similar and / or structurally similar elements).
[0020] Figure 1 is a schematic cross-sectional view of a superficially porous composite particle according to an embodiment of the present disclosure.
[0021] Figure 2 is a schematic cross-sectional view of a superficially porous composite particle according to another embodiment of the present disclosure.
[0022] Figure 3 is a schematic cross-sectional view of a superficially porous composite particle according to another embodiment of the present disclosure.
[0023] Figure 4 is a schematic cross-sectional view of a superficially porous composite particle according to another embodiment of the present disclosure.
[0024] Figure 5 is a schematic cross-sectional view of a superficially porous composite particle according to another embodiment of the present disclosure.
[0025] Figure 6 is a schematic cross-sectional view of a superficially porous composite particle according to another embodiment of the present disclosure. DETAILED DESCRIPTION
[0026] The present disclosure relates to surface porous composite particles, which include a non-porous polymer particle core having a modified surface, a non-porous organic-inorganic hybrid material in contact with the modified surface, and a porous inorganic shell material in contact with the non-porous organic-inorganic hybrid material. That is, an embodiment of the present disclosure relates to a composite particle, which includes a non-porous polymer (e.g., organic material) particle core having a modified surface (e.g., a silyl-modified surface), a non-porous organic-inorganic hybrid material in contact with the modified surface, and a porous inorganic shell material in contact with the non-porous organic-inorganic hybrid material. In some embodiments, the surface porous composite particles of the present disclosure also include a bonding material in contact with one or more of the modified surface, the non-porous organic-inorganic hybrid material, and / or the porous inorganic shell material.
[0027] like Figure 1As shown, a composite particle 100 according to an embodiment of the present disclosure is provided. The composite particle 100 has a nonporous polymer particle core 110, a modified surface 120 of the nonporous polymer particle core 110, an organic-inorganic hybrid nonporous material 130, and an inorganic porous shell material 150. The inorganic porous shell material 150 is deposited or grown on the organic-inorganic hybrid nonporous material 130. The organic-inorganic hybrid material 130 is deposited or grown on the modified surface 120.
[0028] The composite particles of the present invention are generally spherical. The diameter of the composite particles of the present invention is generally in the range of 1 micron to 14 microns, more generally in the range of 1 micron to 6 microns. The particle diameter is measured herein by dispersing the sample in methanol containing 5% lithium chloride using a Coulter counter (Beckman Coulter, Multisizer 4e Coulter Counter, Brea, CA, USA). For each sample, a count of more than 70,000 particles was run using a 30 μm aperture in volume mode. Using the Coulter principle, the volume of the particle is converted into a diameter, wherein the particle diameter is an equivalent spherical diameter, and the equivalent spherical diameter is the diameter of a sphere having the same volume as the volume of the particle. The particle diameter is measured as the 50% cumulative diameter of the particle size distribution based on volume.
[0029] The composite particles of the present disclosure have a non-porous polymer core that has better stability even at a pH greater than 12 than conventional core-shell particles having a silica core.
[0030] The composite particles of the present disclosure are also generally narrowly distributed in size. As defined herein, a collection of particles is "narrowly distributed in size" when the ratio of the 90% cumulative volume diameter divided by the 10% cumulative volume diameter is less than 1.4 when measured with a Beckman Coulter, Multisizer 4e Coulter Counter.
[0031] Nonporous polymer core
[0032] The polymer particle core (e.g., 110, Figure 1 ) comprises at least one organic polymer. The organic polymer core typically contains greater than 95% organic polymer, more typically greater than 97.5% organic polymer, and even more typically greater than 99% organic polymer.
[0033] The polymer particle core is non-porous, which is defined herein to mean that the polymer particle core has a pore volume of less than 0.1 cc / g. Preferably, in some embodiments, the organic polymer core has a pore volume of less than 0.05 cc / g, preferably less than 0.02 cc / g. The pore volume is determined based on a multi-point nitrogen adsorption experiment (Micromeritics ASAP2400; Micromeritics Instruments Inc., Norcross, GA) using methods known in the art.
[0034] The diameter of the polymer core is typically in the range of, for example, 1 micron to 10 microns, more typically 1 micron to 5 microns. The polymer core is typically of narrow size distribution.
[0035] Basically, the polymer particle cores for use in the present disclosure include those composed of carbon and hydrogen, those composed of carbon, hydrogen and oxygen, those composed of carbon, hydrogen and nitrogen, and those composed of carbon, hydrogen, nitrogen and oxygen. The backbone of the organic polymer chain forming the polymer core may contain CC, CO, CN and / or ON covalent bonds. In some embodiments (e.g., in the case of polymers formed by free radical polymerization of vinyl groups), the backbone of at least one organic polymer chain may contain only CC covalent bonds.
[0036] As mentioned above, the polymer core for the present disclosure comprises at least one organic polymer. The at least one organic polymer comprises the residues of one or more organic monomers. The one or more organic monomer residues forming the at least one organic polymer may be selected from the residues of hydrophobic organic monomers, the residues of hydrophilic organic monomers, or a mixture of the residues of hydrophobic organic monomers and the residues of hydrophilic organic monomers.
[0037] The hydrophobic organic monomer may be selected from, for example, C2-C18 olefin monomers and / or monomers including C6-C18 monocyclic or polycyclic carbocyclic groups (e.g., phenyl groups, phenylene groups, naphthalene groups, etc.). Specific examples of hydrophobic organic monomers include, for example, monofunctional and polyfunctional aromatic monomers such as styrene, alkyl-substituted styrene, halogen-substituted styrene, divinylbenzene, and vinylbenzyl chloride; monofunctional and polyfunctional olefin monomers such as ethylene, propylene, or butylene; monofunctional and polyfunctional fluorinated monomers such as vinyl fluoride, 1,1-(difluoroethylene), tetrafluoroethylene, trifluorochloroethylene, hexafluoropropylene, perfluoropropyl vinyl ether, or perfluoromethyl vinyl ether; monomers having higher alkyl or carbon atoms; Monofunctional or multifunctional acrylate monomers having a cyclic group, for example, a monofunctional or multifunctional acrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group; monofunctional or multifunctional methacrylate monomers having a higher alkyl or carbocyclic group, for example, a monofunctional or multifunctional methacrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group, and the like.
[0038] The hydrophilic organic monomer can be selected from, for example, a monofunctional or multifunctional organic monomer having an amide group, a monofunctional or multifunctional organic monomer having an ester group, a monofunctional or multifunctional organic monomer having a carbonate group, a monofunctional or multifunctional organic monomer having a carbamate group, a monofunctional or multifunctional organic monomer having a urea group, a monofunctional or multifunctional organic monomer having a hydroxyl group, and a monofunctional or multifunctional organic monomer having a nitrogen-containing heterocyclic group, etc. Specific examples of the hydrophilic organic monomer include, for example, vinyl pyridine, N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl caprolactam, lower alkyl acrylates (e.g., methyl acrylate, ethyl acrylate, etc.), lower alkyl methacrylates (e.g., methyl methacrylate, ethyl methacrylate, etc.), vinyl acetate, acrylamide or methacrylamide monomers, hydroxypolyethoxy allyl ether monomers, ethoxyethyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, methylenebisacrylamide, allyl methacrylate, or diallyl maleate.
[0039] In various embodiments, the nonporous polymer core includes residues of a multifunctional hydrophobic organic monomer such as divinylbenzene and / or a multifunctional hydrophilic organic monomer such as ethylene glycol dimethacrylate, methylenebisacrylamide, or allyl methacrylate to provide crosslinking in the organic copolymer. In certain embodiments, DVB 80 may be employed, which is an organic monomer mixture comprising divinylbenzene (80%) and a mixture of ethyl-styrene isomers, diethylbenzene, and may also include other isomers.
[0040] In various embodiments, the polymer core may include only residues of multifunctional organic monomers. In various embodiments, the polymer may include residues of both multifunctional organic monomers and monofunctional organic monomers.
[0041] The present inventors have discovered that in some embodiments, the porosity of a material formed from a polymer containing multifunctional organic monomer residues can be reduced by adding monofunctional organic monomer residues to the polymer, or the porosity of a material formed from a polymer containing multifunctional organic monomer residues and monofunctional organic monomer residues can be reduced by increasing the amount of monofunctional organic monomer residues relative to the multifunctional organic monomer residues in the polymer. For example, it has been found that a polymer particle core formed from DVB 80 (which is formed from an organic polymer containing 80% multifunctional divinylbenzene monomer residues and monofunctional ethylstyrene monomer residues, as described above) has a porosity of about 0.015 cc / g, while an organic polymer core formed from DVB 80 and styrene (which contains multifunctional divinylbenzene monomer residues, monofunctional ethylstyrene monomer residues, and additional monofunctional styrene monomer residues) has a porosity of less than 0.007 cc / g.
[0042] In some embodiments, a polymer particle core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is formed by an organic homopolymer containing only a multifunctional organic monomer residue. In some embodiments, an organic polymer core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is also formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, but wherein the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is increased relative to the central core region. In a specific example, an organic polymer core is produced, wherein the central region of the core is formed by DVB and styrene, and the outer region of the core is formed by DVB. In other embodiments, relative to the central core region, the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is reduced.
[0043] In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of a multifunctional organic monomer but not residues of a monofunctional organic monomer. In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of both multifunctional organic monomers and monofunctional organic monomers.
[0044] The polymer forming the polymer particle core can be prepared by a variety of methods and mechanisms, including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In a particularly advantageous embodiment, the nonporous polymer particle core is prepared via free radical polymerization.
[0045] In some embodiments, the polymer particle core of the present disclosure can be prepared by a dispersion polymerization method, in which a homogeneous solution is formed, wherein monomers, initiators, and stabilizers are combined in a solvent or solvent mixture. As the polymerization proceeds, the initially formed polymer precipitates out of the homogeneous solution to form precipitated nuclei. The formed precipitated nuclei still carry reactive sites, such as free radicals, which allow them to keep growing by continuously capturing and incorporating monomers and / or oligomers from the solution.
[0046] In an exemplary method based on free radical polymerization, one or more solvents and one or more stabilizers are purged with nitrogen to remove dissolved oxygen. Then, one or more monomers (including at least one multifunctional monomer) and a free radical polymerization initiator are added. Usually, under stirring, free radical polymerization is initiated by increasing the temperature for several hours. Based on the desired particle diameter, additional free radical polymerization initiators and additional monomers can be added to the reaction mixture to allow the particles to further grow to the desired size. After the reaction, the particles can be thoroughly washed and dried under vacuum.
[0047] Any free radical initiator compatible with the organic phase can be used alone or in a mixture of such free radical initiators. In a specific embodiment, the free radical initiator can be thermally activated or photoactivated. In a specific embodiment, the free radical initiator is a peroxide, peracetic acid, persulfate, azo initiator or a mixture thereof.
[0048] In the case where the initiator is a thermal initiator, the resulting solution can then be heated to an elevated temperature with stirring to activate the thermal initiator and maintained at the elevated temperature until polymerization is complete. In the case where the initiator is a photoinitiator, the resulting solution can then be irradiated with light of a suitable wavelength with stirring to activate the photoinitiator and maintained until polymerization is complete. Suitable organic monomers for the organic phase are as described above.
[0049] Solvent systems used to form polymer particle cores include methanol, ethanol, isopropanol, 2-methoxyethanol, water, acetonitrile, p-xylene, and toluene.
[0050] Stabilizers that can be used to form the polymer particle core include, for example, polyvinyl pyrrolidone (PVP); nonionic surfactants, including alkylphenol ethoxylates (e.g., Triton™ N-57, available from Dow Chemical); polyvinyl alcohol (PVA), such as Selvol TMPolyvinyl alcohol solution (available from Sekisui Special Chemicals); modified celluloses, including alkyl-modified celluloses such as methyl cellulose (e.g. Methocel TM , available from DuPont); and a hydrophobically modified cellulose hydroxyethyl cellulose stabilizer, such as Natrosol TM cetyl modified hydroxyethyl cellulose (available from Ashland); and ionic surfactants, including sodium alkyl sulfates, such as sodium dodecyl sulfate (SDS) and sodium oleyl sulfate, and the like.
[0051] In a specific embodiment of the nonporous polymer particle core formation, the monomers are a combination of DVB and styrene, the initiator is 2,2'-azobis(2-methylpropionitrile) (AIBN), the solvent system is a combination of reagent alcohol and p-xylene, and the stabilizer is polyvinylpyrrolidone (PVP 40).
[0052] Once formed, the organic polymer core may contain surface moieties from which further polymerization may be carried out. For example, nonporous polymer particle cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, or acryloxy moieties, etc.) from which further core growth may be carried out. Such further polymerization may be used to increase the size of a given batch of polymer particle cores by adding additional thickness of nonporous organic polymer to previously formed nonporous polymer particle cores.
[0053] In a specific embodiment of nonporous polymer particle core growth, the monomer is DVB, the solvent is reagent alcohol, and the stabilizer is polyvinylpyrrolidone (PVP 40).
[0054] Surface modified nonporous polymer core
[0055] The superficially porous polymer particles according to the present technology include a modified surface (e.g., 120, Figure 1 ). In some embodiments, the modified surface of the nonporous polymer particle core can form a covalent bond or an electrostatic bond with a subsequently applied nonporous organic-inorganic hybrid material. In certain embodiments, the modified surface of the nonporous polymer core is a silyl-modified surface. The silyl-modified surface can include a first functional group and a second functional group. For example, the first functional group can be a reactive silane (e.g., an alkoxy group), and the second functional group can be an organic polymerizable group (e.g., a vinyl group).
[0056] In some embodiments, the modified surface of the nonporous polymer particle core may have a thickness in the range of 1 nm to 300 nm, for example, any thickness in the range of 1 nm to 3 nm to 10 nm to 30 nm to 100 nm to 300 nm (i.e., in a range between any two of the foregoing values).
[0057] In some embodiments, the modified surface includes a surface polymer, which may include a functional group covalently bonded or electrostatically bonded to an organic-inorganic hybrid nonporous shell. Examples of functional groups electrostatically bonded to an organic-inorganic hybrid nonporous shell include amide functional groups and amine functional groups. In this regard, the organic-inorganic hybrid nonporous material described herein is weakly acidic in nature, and therefore tends to be deprotonated and negatively charged, while the amide functional group or amine functional group described herein is alkaline in nature, and therefore tends to be protonated and positively charged. Examples of functional groups covalently bonded to an organic-inorganic hybrid nonporous shell include organosilane functional groups and organometallic functional groups, such as organotitanium functional groups and organozirconium functional groups. As used herein, an organosilane functional group is a functional group having at least one Si-C bond. Similarly, an organotitanium functional group is a functional group having at least one Ti-C bond, and an organozirconium functional group is a functional group having at least one Zr-C bond.
[0058] In some embodiments, the modified surface includes a surface polymer that may include monomer residues covalently or electrostatically bonded to the organic-inorganic hybrid nonporous shell. Examples of monomer residues electrostatically bonded to the organic-inorganic hybrid nonporous shell include amide monomer residues and amine monomer residues. Examples of monomer residues covalently bonded to the organic-inorganic hybrid nonporous shell include organosilane monomer residues, organotitanium monomer residues, and organozirconium monomer residues. As used herein, an organosilane monomer residue is a monomer residue having at least one Si-C bond, an organotitanium monomer residue is a monomer residue having at least one Ti-C bond, and an organozirconium monomer residue is a monomer residue having at least one Zr-C bond.
[0059] The surface polymer may comprise, for example, polymer chains grafted onto a nonporous polymer core.
[0060] The surface polymer may comprise, for example, a cross-linked polymer network formed on a non-porous polymer particle core.
[0061] The surface polymers can be prepared by a number of methods and mechanisms including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In particularly advantageous embodiments, the nonporous organic polymer core is prepared via free radical polymerization.
[0062] As mentioned above, the polymer particle core may contain surface moieties from which further polymerization may be carried out. For example, organic polymer cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, acryloxy moieties, etc.) from which polymerization of surface polymers may be carried out. The polymer chains may be derived from monofunctional monomers. The crosslinked polymer network may be formed from multifunctional monomers. In addition to multifunctional monomers, monofunctional monomers may also be included in such crosslinked polymer networks.
[0063] As described above, surface polymers include those comprising amide monomer residues. Examples of amide monomer residues include amide monomer residues having the formula: wherein n is an integer from 1 to 3 (i.e., N-vinylpyrrolidone, N-vinyl-2-piperidone, or N-vinylcaprolactam). Examples of amide monomer residues also include those having the formula An amide monomer residue, wherein R1 is selected from C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene, and wherein R2 is selected from H, C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene.
[0064] As also described above, surface polymers include those comprising amine monomer residues. Examples of amine monomer residues include aminoalkyl acrylates, aminoalkyl methacrylates, dialkylaminoalkyl acrylates, or dialkylaminoalkyl methacrylates, including amino-C1-C4-alkyl acrylates, amino-C1-C4-alkyl methacrylates, di-C1-C4-alkylamino-C1-C4-alkyl acrylates, di-C1-C4-alkylamino-C1-C4-alkyl methacrylates, such as 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 2-(N,N-dimethylamino)ethyl acrylate, 2-(N,N-dimethylamino)ethyl methacrylate, 2-(N,N-diethylamino)ethyl methacrylate, or 2-diisopropylaminoethyl methacrylate.
[0065] As further described above, examples of surface polymers also include those comprising silane monomer residues electrostatically bonded to the nonporous organic-inorganic hybrid material. In some embodiments, the surface polymer comprises residues of one or more free radically polymerizable organosilane monomers.
[0066] Specific examples of free radical polymerizable organosilane monomers include unsaturated organosilane monomers (e.g., unsaturated organoalkoxysilane monomers, unsaturated organochlorosilane monomers, etc.), such as alkenyl or alkynyl functionalized organosilane monomers (e.g., alkenyl or alkynyl functionalized organoalkoxysilane monomers, alkenyl or alkynyl functionalized organochlorosilane monomers, etc.). Specific alkenyl functionalized organoalkoxysilane monomers include those having vinyl groups, methacryloxy groups, and acryloxy groups. Specific examples include 3-(trimethoxysilyl)propyl methacrylate (also known as 3-methacryloxypropyltrimethoxysilane or MAPTMOS), methacryloxypropyltriethoxysilane, methacryloxypropyltrichlorosilane, vinyltriethoxysilane (VTES), vinyltrimethoxysilane, N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (3-acryloxypropyl)trimethoxysilane, O-(methacryloxyethyl)-N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, -(triethoxysilylpropyl)urethane, N-(3-methacryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyltri(methoxyethoxy)silane, 3-(N-phenylvinylmethyl-2-aminoethylamino)propyltrimethoxysilane hydrochloride, etc.
[0067] In a specific embodiment of the method for forming a surface-modified nonporous organic polymer core, an organosilane polymer, specifically a poly(styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane), is formed by copolymerizing a styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane monomer (wherein R is a C1-C4 alkyl) with a residual vinyl group (e.g., a residue of divinylbenzene) on the nonporous organic polymer core. Examples of styryl organosilane monomers include styrylethyltrimethoxysilane and styryltrimethoxysilane.
[0068] Nonporous organic-inorganic hybrid materials
[0069] As previously mentioned, the present disclosure relates to composite particles in which a nonporous organic-inorganic hybrid material (e.g., 130, Figure 1 ) is in contact with the modified surface of the non-porous polymer core.
[0070] In some embodiments, the nonporous organic-inorganic hybrid material may have a thickness in the range of, for example, 10 nm to 200 nm, typically 25 nm to 100 nm. In some embodiments, the nonporous organic-inorganic hybrid material may have a pore volume of, for example, less than 0.1 cc / g (e.g., 0.05 cc / g), typically less than 0.02 cc / g.
[0071] "Organic-inorganic hybrid" materials include inorganic-based structures in which organic functional groups are integrated with both the internal or "framework" inorganic structure and the surface of the hybrid material. The inorganic portion of the hybrid material can be, for example, silicon dioxide, aluminum oxide, titanium, cerium or zirconium or their oxides, or a ceramic material. Exemplary hybrid materials are shown in U.S. Patents 4,017,528, 6,528,167, 6,686,035, 7,175,913 and 7,919,177, the disclosures of which are hereby incorporated in their entirety.
[0072] In some embodiments, the nonporous organic-inorganic hybrid material may include a silicon-based organic-inorganic hybrid material, which includes a hybrid region, wherein the silicon-based nonporous organic-inorganic hybrid material includes a silicon atom having one or more silicon-oxygen bonds and one or more silicon-carbon bonds. In some cases, the hybrid region may include a substituted or unsubstituted alkylene, alkenylene, alkynylene or arylene moiety bridging two or more silicon atoms. For example, the hybrid region may include a substituted or unsubstituted C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene moiety bridging two or more silicon atoms. In some embodiments, the hybrid region may include a substituted or unsubstituted C1-C6 alkylene moiety bridging two or more silicon atoms, including a methylene, dimethylene or trimethylene moiety bridging two silicon atoms. In some embodiments, the hybrid region may include a ≡Si-(CH2)n-Si≡ portion, where n is an integer and may be equal to 1, 2, 3, 4 or greater. In some embodiments, the nonporous organic-inorganic hybrid material may include a silicon-based nonporous organic-inorganic hybrid material that includes an inorganic region in which the material includes silicon atoms having four silicon-oxygen bonds in addition to a hybrid region in which the material includes silicon atoms having one or more silicon-oxygen bonds and one or more silicon-carbon bonds.
[0073] In various embodiments, the nonporous organic-inorganic hybrid material can be formed by hydrolytic condensation of one or more organosilane compounds on a surface modified nonporous organic polymer core such as those described above. As used herein, an organosilane compound is a silane compound having at least one Si-C bond.
[0074] The organosilane compound may include, for example, (a) one or more organosilane compounds of the formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, wherein at least one of Z1, Z2, Z3 and Z4 is C1-C4 alkyl, examples of which include alkyl-trialkoxysilanes, such as C1-C4-alkyl-tri-C1-C4-alkoxysilanes, including methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane or ethyltriethoxysilane, and dialkyl-dialkoxysilanes, such as C1-C4-dialkyl-di-C1-C4-alkoxysilanes, such as dimethyldiethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane or diethyldiethoxysilane. and many other possibilities, and / or (b) one or more organosilane compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6, wherein Z1, Z2 and Z3 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z1, Z2 and Z3 can be C1-C4 alkyl, wherein Z4, Z5 and Z6 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z4, Z5 and Z6 can be C1-C4 alkyl, and wherein R is an organic group, for example selected from C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene, typically C1-C4 alkylene, typically C1-C6 alkylene. Examples of compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6 include bis(trialkoxysilyl)alkanes, for example, bis(tri-C1-C4-alkoxysilyl)C1-C4-alkanes such as bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane and bis(triethoxysilyl)ethane as well as many other possibilities.
[0075] In some embodiments, one or more additional non-organosilane compounds can be hydrolyzed and condensed with one or more organosilane compounds. Such compounds include silane compounds of formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy and C1-C4 alkylamino. In certain embodiments, the additional silane compound is tetra-C1-C4-alkoxysilane, such as tetramethoxysilane or tetraethoxysilane.
[0076] In some embodiments, the nonporous organic-inorganic hybrid material can be formed by hydrolytic condensation of the following substances on the modified surface of the nonporous organic polymer core as described above: (a) one or more alkoxysilanes, such as tetraalkoxysilanes (e.g., tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), etc.), and (b) one or more organosilanes, for example, selected from bis(trialkoxysilyl)alkanes (e.g., bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane (BTEE), etc.) and / or alkyltrialkoxysilanes (e.g., methyltrimethoxysilane, methyltriethoxysilane (MTOS), ethyltriethoxysilane, etc.). In the case where the plurality of silane compounds includes one or more bis(trialkoxysilyl)alkanes, an alkyl-bridged nonporous organic-inorganic hybrid material is prepared, which can provide various advantages over conventional silica-based materials, including chemical and mechanical stability. When BTEE is used as a monomer, the resulting material is an ethylene bridged hybrid (BEH) material. A specific BEH material can be formed by the hydrolytic condensation of TEOS and BTEE.
[0077] In some embodiments, a plurality of silane compounds as described above (e.g., a plurality of silane compounds including one or more organosilanes and one or more tetraalkoxysilanes) are partially condensed to form a polyalkoxyorganosiloxane oligomer, which is then hydrolyzed and condensed onto the modified surface of the nonporous organic polymer core. For example, BTEE and TEOS may be partially condensed to form a polyethoxyorganosiloxane oligomer (PEOS), which is hydrolyzed and condensed onto the modified surface of the nonporous organic polymer core.
[0078] In various embodiments, the nonporous organic-inorganic hybrid material can be formed by producing (usually in a series of steps) a reaction mixture comprising the following components: a surface-modified nonporous organic polymer core, ethanol, one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)), water, and a basic or acidic catalyst, the catalyst being used to promote the hydrolysis and condensation of the silanes on the modified surface of the nonporous organic polymer core of the nonporous organic-inorganic hybrid material. In some embodiments, the hydrolysis is carried out at room temperature. In some embodiments, the mixture is heated to drive the hydrolysis reaction to completion. In some embodiments, the mixture is stirred. After the organic-inorganic hybrid nonporous material is formed, the resulting particles can be washed and dried.
[0079] In other embodiments, nonporous organic-inorganic hybrid materials can be formed by the interaction between a template surfactant (e.g., and an ionic surfactant such as hexadecyltrimethylammonium bromide (CTAB) or trioctylmethylammonium bromide (TOMB)) and one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)) during the continuous addition of silanes, alkaline catalysts, and template surfactants to the modified surface of a nonporous organic polymer core. The process results in continuous silane hydrolysis and condensation of organic-inorganic hybrid reaction products on the core. The reaction can be carried out at room temperature or elevated temperature.
[0080] As described above, one or more organosilanes (e.g., TEOS and BTEE, or PEOS) can be hydrolyzed in the presence of a surface-modified nonporous (NP) organic polymer core having a surface polymer including monomer residues of an amide monomer and / or a silane monomer, so that the hydrolyzed organosilanes form a nonporous organic-inorganic hybrid material on the modified surface of the nonporous polymer core.
[0081] Porous Inorganic Materials
[0082] As previously mentioned, the present disclosure relates to composite particles in which a porous inorganic material is in contact with a nonporous organic-inorganic hybrid nonporous material. Figure 1 As shown in the composite particle 100 in FIG. 1 , a porous inorganic material 150 is deposited or grown on a nonporous organic-inorganic hybrid material 130. The nonporous organic-inorganic hybrid material 130 is deposited or grown on the modified surface 120. The pores 106 extend within the inorganic porous shell material 150. Thus, the particle 100 has a nonporous central portion (e.g., core 110, nonporous organic-inorganic hybrid material 130) and a porous shell portion (e.g., porous inorganic material 150).
[0083] The porous inorganic material (i.e., material 150) has a pore volume of 0.1 cc / g or greater (e.g., 0.2 cc / g for material 150), preferably greater than 0.65 cc / g. In various embodiments, the pore volume of the porous inorganic material is substantially greater than 0.15 cc / g of the porous inorganic material, for example, the pore volume is in the range of 0.2 cc / g to 1.5 cc / g of the porous inorganic material, preferably 0.4 cc / g to 0.75 cc / g of the porous inorganic material.
[0084] In some embodiments, the thickness of the porous inorganic material may be, for example, in the range of 0.1 micrometer to 4 micrometers, typically in the range of 0.1 micrometer to 2 micrometers, more typically in the range of 0.1 micrometer to 1.2 micrometers. In some embodiments, the ratio of the diameter of the core to the diameter of the entire particle may be, for example, in the range of 0.3:1 to 0.99:1, more typically 0.65:1 to 0.8:0.9.
[0085] In some embodiments, the porous inorganic material may include a silicon-based inorganic material including a region where the material includes silicon atoms having one or more silicon-oxygen bonds. For example, the porous inorganic material may include a silicon-based inorganic material including a region where the material includes silicon atoms having four silicon-oxygen bonds.
[0086] In some embodiments, the nonporous organic-inorganic hybrid material can be deposited or grown on the composite particles. Figure 2 As shown in the composite particle 200, the non-porous organic-inorganic hybrid material 230b is deposited or grown on the porous inorganic material 250 having pores 206. The porous inorganic material 250 is deposited or grown on the non-porous organic-inorganic hybrid material 230a, which can be the same material as 230b or a different material from 230b. The non-porous organic-inorganic hybrid material 230a is deposited or grown on the modified surface 220 of the non-porous polymer particle core 210.
[0087] The nonporous organic-inorganic hybrid material 230b protects the underlying porous inorganic material 250. That is, the nonporous organic-inorganic hybrid material 230b prevents or reduces dissolution of the porous inorganic material 250 by forming a barrier layer around the porous inorganic material 250 outside the composite particle 200.
[0088] Bonding material
[0089] As previously mentioned, in some embodiments, the composite particles as disclosed herein may additionally include a binding material that modifies one or more portions of the composite particles. For example, modified surfaces, nonporous organic-inorganic hybrid materials and / or porous inorganic materials can be modified with binding materials. The modification can be an intrinsic modification (i.e., a binding material is included when a portion of the deposited or grown particles is deposited), a surface modification (i.e., the modification is applied to the exposed surface of the particles) or a combination thereof. It should be noted that the intrinsic modification of porous inorganic materials with binding materials (e.g., silanes) can cause the porous inorganic materials to be transformed into inorganic-organic hybrid materials. That is, the incorporation of binding materials when depositing inorganic materials can cause the conversion / generation of a mixed material (e.g., from the incorporation of binding materials) comprising both inorganic and organic materials.
[0090] like Figure 3As shown, in an embodiment of a composite particle 300 having a nonporous polymer core 310 and a modified surface 320, a binding material is applied to an outer portion of the particle 300. Specifically, the nonporous organic-inorganic hybrid material 330b is surface-modified with a binding material 340; a layer or region extending from the nonporous organic-inorganic hybrid material 330b is formed. The nonporous organic-inorganic hybrid material 330b is deposited or grown on a porous inorganic material 350, which is also in contact with the nonporous organic-inorganic hybrid material 330a. The nonporous organic-inorganic hybrid material 330a may not be in contact with the porous inorganic material 350, wherein the pores 306 extend to the surface of the nonporous organic-inorganic hybrid material 330a. In the case where the nonporous organic-inorganic hybrid nonporous material 330a is not in contact with the porous inorganic material 350, the nonporous organic-inorganic hybrid nonporous material 330a may also be surface-modified with the binding material 340, although this is not required. In some embodiments, the nonporous organic-inorganic hybrid material 330b is also deposited or grown on the organic-inorganic hybrid nonporous material 330a, and the nonporous organic-inorganic hybrid material 330b is surface-modified with the binding material 340. In these cases, the nonporous organic-inorganic hybrid material 330b surface-modified with the binding material 340 extends within the pore 306 to the organic-inorganic hybrid nonporous material 330a.
[0091] In some embodiments, the nonporous organic-inorganic hybrid material 330a and the nonporous organic-inorganic hybrid material 330b are the same material (i.e., chemically and structurally the same). However, this need not be the case. In some embodiments, the nonporous organic-inorganic hybrid material 330a is different from the nonporous organic-inorganic hybrid material 330b added after the growth of the porous inorganic material 350. For example, the nonporous organic-inorganic hybrid material 330a and the nonporous organic-inorganic hybrid material 330b can be chemically different and / or can have different microstructures. In some embodiments, the pore volume of the nonporous organic-inorganic hybrid material 330b may be different from the pore volume of the organic-inorganic hybrid material 350a. However, both organic-inorganic hybrid materials 330a and 330b are nonporous and therefore have a pore volume less than 0.1cc / g. For example, in one embodiment, the nonporous organic-inorganic hybrid material 330b may have a pore volume of 0.02 cc / g, while the nonporous organic-inorganic hybrid material 330a has a pore volume of 0.05 cc / g.
[0092] In another embodiment (composite particle 400), and as Figure 4As shown, the binding material can be incorporated intrinsically and through surface modification. Composite particle 400 includes a nonporous polymer core 410 having a modified surface 420. Deposited or grown on modified surface 420 is a nonporous organic-inorganic hybrid material 430a. Porous material 450 is in contact with both nonporous organic-inorganic hybrid material 430a and nonporous organic-inorganic hybrid material 430b, which can be deposited on porous material 450.
[0093] The nonporous organic-inorganic hybrid material 430b is surface-modified with a binding material 440a. In addition, the nonporous organic-inorganic hybrid material 430a and the porous material 450 are intrinsically modified with a binding material 440b. That is, the binding material 440b is incorporated into at least a portion of the nonporous organic-inorganic hybrid material 430a and at least a portion of the porous material 450. It should be noted that when the binding material 440b is incorporated into a portion of the porous material 450, its incorporation can cause the material to transform. For example, in an embodiment where the porous material is an inorganic material before incorporation 440b, the simultaneous deposition of the porous inorganic material and the binding material results in a transformation to a porous inorganic-organic hybrid material.
[0094] In some embodiments (not shown), the bonding material 440b may be included in the organic-inorganic hybrid nonporous material 430a in a gradient form (i.e., the concentration of the bonding material 440b varies with the thickness). The nonporous organic-inorganic hybrid material 430a (not in contact with the porous material 450) and the nonporous organic-inorganic hybrid material 440b are additionally surface-modified with the bonding material 440a. The nonporous organic-inorganic hybrid material 430a is in contact with (e.g., has been modified with) the bonding materials 440a and 440b, and a portion of the nonporous organic-inorganic hybrid material 430b and the porous material 450 is in contact with (e.g., has been modified with) the bonding material 440a.
[0095] In some embodiments, the bonding material 440b incorporated into at least a portion of the nonporous organic-inorganic hybrid material 430a and the porous material 450 is the same as the bonding material 440a added after the growth of the nonporous organic-inorganic hybrid material 430b. However, this need not be the case. In some embodiments, the bonding material 440b within the nonporous organic-inorganic hybrid material 430a is different from the bonding material 440a added after the growth of the nonporous organic-inorganic hybrid material 430b (e.g., end caps are supplied externally to the hybrid material 430b, or charges are added to create a charged surface).
[0096] In some embodiments, the nonporous organic-inorganic hybrid material 430a and the nonporous organic-inorganic hybrid material 430b are the same material (i.e., chemically, structurally the same). However, this need not be the case. In some embodiments, the nonporous organic-inorganic hybrid material 430a is different from the nonporous organic-inorganic hybrid material 430b added after the growth of the porous material 450. For example, the nonporous organic-inorganic hybrid material 430a and the nonporous organic-inorganic hybrid material 430b may be chemically different and / or may have different microstructures.
[0097] In another embodiment (composite particle 500 having a nonporous polymer core 510, see Figure 5 ), the nonporous organic-inorganic hybrid material 530b is surface-modified with a binding material 540a. In addition, at least a portion of the modified surface 520, the nonporous organic-inorganic hybrid material 530a, and the porous material 550 are intrinsically modified with a binding material 540b. That is, the binding material 540b is incorporated into at least a portion of the porous material 550, the nonporous organic-inorganic hybrid material 530a, and the modified surface 520. In some embodiments (not shown), the binding material 540b may be included in the porous material 550 and / or the nonporous organic-inorganic hybrid material 530b in a gradient form (i.e., the concentration of the binding material 540b varies with the thickness of the particle 500).
[0098] It should be noted that the porous material 550 is a porous inorganic-organic hybrid material. That is, the incorporation of the binding material 540b into the porous inorganic material (or co-deposition therewith) results in the formation of the porous inorganic-organic hybrid material.
[0099] The non-porous organic-inorganic hybrid material 530a (not in contact with the porous material 550) and the non-porous organic-inorganic hybrid material 540b are additionally surface-modified with the bonding material 540a. Figure 5 It can be seen that the modified surface 520 is in contact with the nonporous organic-inorganic hybrid material 530a, both of which are in contact with the bonding material 540b. The nonporous organic-inorganic hybrid material 530b is in contact with the porous material 550, which is also in contact with the nonporous organic-inorganic hybrid material 530a. The nonporous organic-inorganic hybrid material 530b and the nonporous organic-inorganic hybrid material 530a are both in contact with the bonding material 540a (having been surface-modified). The nonporous organic-inorganic hybrid materials 530b and 530a can also be in contact with the bonding material 540a and the bonding material 540b.
[0100] In some embodiments, the bonding material 540b incorporated into the modified surface 520 and the nonporous organic-inorganic hybrid material 530a is the same as the bonding material 540a added after the growth of the nonporous organic-inorganic hybrid material 530b. However, this need not be the case. In some embodiments, the bonding material 540b in the modified surface 520 and the nonporous organic-inorganic hybrid material 530a is different from the bonding material 540a added after the growth of the nonporous organic-inorganic hybrid material 530b (e.g., end caps are supplied externally to the hybrid material 530b, or charges are added to produce a charged surface).
[0101] In some embodiments, the nonporous organic-inorganic hybrid material 530a and the nonporous organic-inorganic hybrid material 530b are the same material (i.e., chemically, structurally the same). However, this need not be the case. In some embodiments, the nonporous organic-inorganic hybrid material 530a is different from the nonporous organic-inorganic hybrid material 530b that is added after the growth of the porous material 550. For example, the nonporous organic-inorganic hybrid material 530a and the nonporous organic-inorganic hybrid material 530b may be chemically different and / or may have different microstructures.
[0102] although Figure 5 Particles 500 are shown with the binder material 540a added after the growth of the porous material 550, but this need not be the case. Figure 6 As shown, in another embodiment, each of the modified surface 620, the nonporous organic-inorganic hybrid material 630a, and the porous material 650 is internally modified with a binding material 640. That is, the binding material 640 is incorporated into at least a portion of one or more of the modified surface 620, the nonporous organic-inorganic hybrid material 630a, and the porous material 650. It should be noted that when the binding material 640 is internally incorporated into a portion of the porous inorganic material, the modified portion is transformed into a porous inorganic-organic hybrid material (e.g., the porous material 650).
[0103] from Figure 6 It can be seen that the modified surface 620 of the nonporous polymer core 610 is in contact with the nonporous organic-inorganic hybrid material 630a, which is also in contact with the porous material 650, which are all in contact with the binding material 640. In addition, the nonporous organic-inorganic hybrid material 630b may also include the binding material 640 (with its intrinsic modification). Although not shown, in some embodiments, the binding material 640 is included in one or more of the nonporous organic-inorganic hybrid nonporous materials 630a, 660b and the porous material 650 in a varying composition (e.g., in a gradient form).
[0104] And, despite Figure 6630a, 630b, and 650 need not be intrinsically modified with the binding material 640. For example, the porous material 650 does not need to be intrinsically modified. That is, the binding material may be incorporated into one or more of the modified surface 620, the nonporous organic-inorganic hybrid material 630a, and the nonporous organic-inorganic hybrid material 630b without incorporating the binding material 640 into the porous material 650. In this case, the porous material 650 will not be intrinsically modified and will be a porous inorganic material in this embodiment.
[0105] In some embodiments, the nonporous organic-inorganic hybrid material 630a and the nonporous organic-inorganic hybrid material 630b are the same material (i.e., chemically, structurally the same). However, this need not be the case. In some embodiments, the nonporous organic-inorganic hybrid material 630a is different from the nonporous organic-inorganic hybrid material 630b that is added after the growth of the porous material 650. For example, the nonporous organic-inorganic hybrid material 630a and the nonporous organic-inorganic hybrid material 630b may be chemically different and / or may have different microstructures.
[0106] The bonding material can be functionalized (e.g., customized or adjusted) for a specific chromatographic separation or mode (obstacle chromatography, HDC, IP-RPLC, WAX). In some cases, at least a portion of the bonding material is a silane. The bonding material can be hydrophobic, hydrophilic, positively and / or negatively charged, or a combination thereof. In some cases, at least a portion of the bonding material can be an ionizable silane. The bonding material can include, but is not limited to, alkyl (e.g., C1 to C20), polyethylene glycol, hydrophilic polymers based on acrylamide and (meth)acrylate, polar groups containing nitrides, nitriles, hydroxyls, negatively and / or positively charged groups, amino, chlorine or alkoxysilanes, or a combination thereof.
[0107] In some embodiments, the bonding material can be uniformly incorporated into the composite particles. The bonding material can be deposited synchronously (i.e., intrinsic modification) and / or can be applied to the outer surface (i.e., surface modification). The bonding material can be incorporated into the composite particles in a gradient form, wherein the bonding material is deposited after the formation of a specific material (e.g., non-porous organic-inorganic hybrid material) has begun but before the deposition / formation of the specific region (e.g., 630a, 630b) of the particle has ended. In some embodiments, the concentration or amount of the bonding material of the non-porous organic-inorganic hybrid material can vary along the thickness of the material. In some cases, the bonding material can be incorporated into the modified surface (e.g., silyl modified surface) as a silane bonding. (See, for example, U.S. Patent Publication US2019 / 0322783, which is incorporated herein by reference). The bonding material can be hydrophobic, hydrophilic, positively charged and / or negatively charged or a combination thereof. In some cases, at least a portion of the bonding material can be an ionizable silane to form a functionalized surface.
[0108] As used herein, the term "gradient" refers to the composition of a particle as viewed from the center of the particle to the surface of the particle. In a gradient material, the composition of the material varies based on the order and concentration of monomers added in a predetermined pattern, such that there is a compositional variation along the radius of the particle, but no discrete shell of material is formed. For example, a material of a polymer particle may have a unique gradient composition across the radius from the particle core to the outermost surface, wherein the compositional gradient includes, but is not limited to, a hydrophobicity / hydrophilicity gradient, a crosslinking ratio gradient, a functional group gradient, a charge ratio gradient, a density gradient, or a combination thereof.
[0109] Chromatographic device
[0110] In some aspects of the present disclosure, the composite particles described herein may be provided in a suitable chromatographic device. To this end, the composite particles described herein may be provided together with a suitable housing. The composite particles and housing may be supplied independently, or the composite particles may be prepackaged in the housing. The housing used according to the present disclosure generally includes a chamber for receiving and holding the composite particles. In various embodiments, the housing may be provided with an inlet and an outlet leading to the chamber and leading out of the chamber.
[0111] Suitable materials of construction for the chromatography housing include inorganic materials, for example, metals such as stainless steel and ceramics such as glass, and synthetic polymeric materials such as polyethylene, polypropylene, polyetheretherketone (PEEK), and polytetrafluoroethylene, among others.
[0112] In certain embodiments, the chromatography housing may include one or more filters for retaining the composite particles in the housing. Exemplary filters may be in the form of, for example, a membrane, a mesh, a frit, or a spherical porous filter.
[0113] In certain embodiments, the chromatographic device is a chromatographic column.
[0114] The present disclosure also provides a kit comprising a composite particle, a housing or a device as described herein, and instructions for use. In one embodiment, the instructions are for a separation device, such as a chromatography column.
[0115] Chromatographic separation
[0116] In some aspects of the present disclosure, the composite particles of the present disclosure can be used for a variety of chromatographic separation methods. Therefore, the chromatographic device and chromatographic set described herein can also be used for such methods. Examples of chromatographic separation methods that can use the composite particles of the present invention include being used for both high pressure liquid chromatography (HPLC) and ultra high pressure liquid chromatography (UHPLC) in different modes. Those modes include but are not limited to affinity separation, hydrophilic interaction chromatography (HILIC) separation, normal phase separation, reverse phase separation, chiral separation, supercritical fluid chromatography SFC separation, perfusion separation, size exclusion chromatography (SEC) separation, ion exchange separation or multi-mode separation.
[0117] The composite particles, devices and kits disclosed herein can be used for chromatographic separation of substances such as small molecules, carbohydrates, antibodies, whole proteins, peptides and / or DNA.
[0118] Such chromatographic separations may include loading a sample onto the composite particles according to the present disclosure, and eluting the adsorbed species from the composite particles with a mobile phase.
[0119] Such chromatographic separations can be performed in conjunction with a variety of aqueous and / or organic mobile phases (i.e., in mobile phases containing water, organic solvents, or a combination of water and organic solvents) and in conjunction with a variety of mobile phase gradients (including gradients of solvent type, temperature, pH, salt concentration, or other parameters).
[0120] The following examples are provided to illustrate how to make composite particles and components thereof according to the present technology. These examples are for illustrative purposes only and should not be considered restrictive. When an amount, concentration or other value or parameter is given as a list of ranges, preferred ranges or upper preferred values and lower preferred values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether the range is disclosed separately. In the case of numerical ranges listed herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within the range. When limiting the range, the scope of the present technology is not intended to be limited to the specific value described.
[0121] Example 1: Non-porous poly(DVB80) particle core
[0122] In this example, an exemplary nonporous core was fabricated. Other methods and other materials may be utilized to fabricate the nonporous polymer core of the composite particles of the present technology.
[0123] The inhibitors in divinylbenzene (80%, technical grade) used in the particle synthesis were removed by passing the monomer through an alumina filter cartridge.
[0124] Primary particle synthesis: In this particle synthesis experiment (Sample 1A in Table 1 below), 65.1 grams of PVP-40, 8.9 grams of Triton N-57, 2452.6 grams of reagent alcohol (905 ethanol, 5% methanol and 5% isopropanol) and 153.3 grams of p-xylene were charged into a 4L round bottom flask reactor equipped with a mechanical stirring device, a condenser and a thermocouple. The mixture was stirred and mixed at 200 RPM, and the dissolved oxygen in the solution was removed by subsurface purging with nitrogen. After the dissolved oxygen was below 1 ppm, 2.1 grams of azobisisobutyronitrile and 105 grams of divinylbenzene were charged to the reaction. The reaction temperature was raised to 70°C and maintained at this temperature for 20 hours. Primary nucleus growth: When the 20 hour reaction time was reached, the temperature was maintained at 70°C and 1.8 grams of azobisisobutyronitrile was added. Subsequently, a solution of 67.6 g of divinylbenzene and 20.3 g of PVP-40 in 202.7 g of reagent alcohol was metered in via a pump at a constant flow rate over 120 minutes. The reaction was continued at 70° C. for at least 12 hours. After the reaction, the particles were separated from the reaction slurry by filtration and subsequently washed with methanol, tetrahydrofuran (THF) and acetone in sequence. The final product was placed in a vacuum oven and dried overnight at 45° C. Approximately 147 g of 1.95 μm particles were obtained.
[0125] To test the effect of adjusting the amount of PVP-40 at the start of the reaction, three different amounts were evaluated (65.1 g - Sample 1A; 48.9 g - Sample 1B; and 109.2 g - Sample 1C). The results are provided in Table 1 below, which show that particle size is inversely correlated with the amount of PVP-40.
[0126]
[0127] Table 1
[0128] Example 2: Nonporous Poly(DVB80-co-styrene) Particle Core
[0129] In this example, an exemplary non-porous core was fabricated that included a polymer core comprising two different polymers. Other methods and other materials may be utilized to fabricate the non-porous polymer core of the composite particles of the present technology.
[0130] The inhibitors in divinylbenzene (80%, technical grade) and styrene used in the particle synthesis were removed by passing the monomers through an alumina filter cartridge.
[0131] Primary Particle Synthesis: In this particle synthesis experiment (Sample 2A), 78.2 grams of PVP-40, 8.9 grams of Triton N-57, 2452.6 grams of reagent alcohol (905 ethanol, 5% methanol and 5% isopropanol) and 153.3 grams of p-xylene were charged into a 4L round bottom flask reactor equipped with a mechanical stirrer, condenser and thermocouple. The mixture was stirred and mixed at 200 RPM, and the dissolved oxygen in the solution was removed by subsurface purging with nitrogen. After the dissolved oxygen was below 1 ppm, 2.1 grams of azobisisobutyronitrile, 42 grams of divinylbenzene (80%, technical grade) and 63.0 grams of styrene were charged to the reaction. The reaction temperature was raised to 70°C and maintained at this temperature for 20 hours.
[0132] Primary nucleus growth: When a reaction time of 20 hours is reached, the temperature is maintained at 70°C and 1.8 g of azobisisobutyronitrile is added. Subsequently, a solution of 67.6 g of divinylbenzene and 19.2 g of PVP-40 in 192.0 g of reagent alcohol is metered in via a pump at a constant flow rate over 120 minutes. The reaction is continued at 70°C for at least 12 hours. After the reaction, the particles are separated from the reaction slurry by filtration and subsequently washed with methanol, tetrahydrofuran (THF) and acetone in sequence. The final product is placed in a vacuum oven and dried overnight at 45°C. Approximately 135 g of 2.2 μm particles are obtained.
[0133] Below, in Table 2, Samples 2A to 2C describe the synthesis of poly(DVB80-co-styrene) particles having different compositions of DVB80 and styrene by adjusting the amounts of DVB80 and styrene charged in the primary core synthesis step of the core growth step.
[0134]
[0135] Table 2
[0136] Example 3: A larger particle core made from another smaller core
[0137] In this example, an exemplary nonporous core was fabricated that included a core fabricated in two stages.Other methods and other materials may be utilized to fabricate the nonporous polymer core of the composite particles of the present technology.
[0138] 120 grams of particles (particle size, 2.32 μm) prepared by the method described in Sample 2D were redispersed in a solution containing 37.0 grams of PVP-40, 4.5 grams of Triton™ N-57, 100.0 grams of p-xylene, and 1234.0 grams of reagent alcohol (90% ethanol, about 5% methanol, and about 5% isopropanol) and then loaded into a 4-liter kettle reactor equipped with a mechanical stirring device, a condenser reactor, and a thermocouple. The slurry was mixed at 200 RPM and nitrogen was purged through the surface to obtain dissolved oxygen below 1 ppm. Once the dissolved oxygen in the solution was below 1 ppm, the nitrogen subsurface sparge was changed to a blanket sparge, the stirring speed was adjusted to 75 RPM, and the reaction temperature was then increased to 70°C. When the reaction temperature reached 70°C, 4.8 grams of divinylbenzene (80%, de-inhibited with alumina) and 3.0 grams of AIBN were added. After 15 minutes, a solution containing 139.5 g of divinylbenzene (80%, with alumina to remove inhibitors), 105.6 g of PVP-40 and 1345.7 g of reagent alcohol was added by a pump at a constant rate over 2 hours. After addition, the reaction was maintained at 70°C for 20 hours. After the reaction, the particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally with acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 250 g of monodisperse 3.0 μm particles were obtained.
[0139] Example 4: Core surface primed with silane functional groups
[0140] In this example, an exemplary primed nonporous core was fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core of the composite particles of the present technology.
[0141] The inhibitors in divinylbenzene (80%, technical grade) and styrylethyltrimethoxysilane were removed by passing through an alumina filter cartridge. The reagent alcohol used in the reaction contained 90% ethanol, about 5% methanol and about 5% isopropanol. In this particle synthesis experiment (see sample 4A in Table 3 below), 44.7 grams of PVP-40 and 165.2 grams of p-xylene were loaded into a 4L round-bottom flask reactor equipped with a mechanical stirring device, a condenser reactor and a thermocouple. A slurry of 145.0 grams of particles (sample 1A, from Example 1) in 1490.7 grams of reagent alcohol was added. The mixture was mixed at 200RPM for 24 hours. The reaction slurry was then purged subsurface with nitrogen to obtain dissolved oxygen below 1ppm. Once the dissolved oxygen in the solution was less than 1ppm, the reaction mixture was heated to 70°C and the stirring speed was adjusted to 75RPM. Then, 2.9 grams of divinylbenzene and 2.5 grams of 2,2'-azobis(2-methylpropionitrile) (AIBN) were added. After mixing for 15 minutes, a solution containing 14.5 grams of styrylethyltrimethoxysilane, 1.5 grams of divinylbenzene and 13.9 grams of PVP-40 in 464.0 grams of reagent alcohol was added at a constant flow rate over 2 hours. After the reaction was maintained at 70°C for a total of 20 hours, the reaction was cooled to below 40°C and the resulting particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 149.0 grams of primed particles were obtained.
[0142] Table 3 provides the synthesis of primer particles with different surface morphologies and primer thicknesses by adjusting the amount of primer monomer and the amount of crosslinker DVB80 used in a number of different samples.
[0143]
[0144] Table 3
[0145] Example 5: Core Surface Primed with Other Functional Groups
[0146] In this example, exemplary primed nonporous cores with various functional groups were fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer cores of the composite particles of the present technology.
[0147] Here, with reference to sample 5A (as shown below), the primer monomer of the primer-free polymer core is replaced. Specifically, the reagent alcohol used in the reaction contains 90% ethanol, about 5% methanol and about 5% isopropanol. In this particle synthesis experiment, 15.4 grams of PVP-40 and 57.0 grams of p-xylene are loaded into a 1L round-bottom flask reactor equipped with a mechanical stirring device, a condenser, a reactor and a thermocouple. Add 50.0 grams of a slurry of particles made in Example 3 in 514.0 grams of reagent alcohol. The mixture was mixed at 200RPM for 24 hours. The reaction slurry was then purged subsurface with nitrogen to obtain dissolved oxygen below 1ppm. Once the dissolved oxygen in the solution is less than 1ppm, the reaction mixture is heated to 70°C and the stirring speed is adjusted to 75RPM. Then, 1.8 grams of divinylbenzene and 0.9 grams of 2,2'-azobis(2-methylpropionitrile) (AIBN) were added. After mixing for 15 minutes, a solution containing 9.0 grams of N-vinyl pyrrolidone, 0.9 grams of divinyl benzene and 3.6 grams of PVP-40 in 120.0 grams of reagent alcohol was added at a constant flow rate over 2 hours. After the reaction was maintained at 70°C for a total of 20 hours, the reaction was cooled to below 40°C and the resulting particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 54.0 grams of primed particles were obtained.
[0148] Samples 5A to 5E, shown below, describe the synthesis of primed particles with different surface functional groups. In each sample, the primer monomer was replaced in the formulation of the primed nonporous polymer core. While the above experiments utilized sample 5A, additional experiments were performed utilizing samples 5B to 5E.
[0149]
[0150] Example 6: Nonporous Hybrid Coating on Trimethoxysilane Primer Core
[0151] In this example, an exemplary primed nonporous core with a hybrid coating was fabricated to form a composite particle according to the present technology.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core with a hybrid coating of the composite particles of the present technology.
[0152] In this particle synthesis experiment (i.e., for Sample 6A), a 5 L round bottom flask reactor equipped with a mechanical stirring device, condenser, reactor, and thermocouple was set up in an ultrasonic bath capable of heating (490 watts). 140.0 grams of silane primed cores (Sample 4A) were redispersed in 1120.0 grams of 200 proof ethanol and then loaded into the reactor. 1120.0 grams of toluene and 26.9 grams of Pluronic F127 and 77.1 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The temperature of the ultrasonic bath was raised to 35°C and ultrasonic treatment was started. Ultrasonic treatment was maintained throughout the coating process. When the temperature of the ultrasonic bath reached 35°C, a solution containing 98.2 g of tetraethyl orthosilicate (TEOS), 41.8 g of 1,2-bis(triethoxysilyl)ethane (BTEE), and 3.5 g of Pluronic F127 in a mixed solvent of 70.0 g of ethanol (200 proof) and 70.0 g of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was maintained at 35°C for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was placed in a vacuum oven and dried overnight at 70°C. 174.0 g of non-porous BEH coated particles (i.e., sample 4A particles coated with non-porous BEH material) were obtained.
[0153] Table 4 below provides the synthesis of nonporous hybrid coated particles (Samples 6A-6H) with different coating thicknesses and surface morphologies by adjusting the amounts of TEOS, BTEE and with or without the use of surfactant.
[0154]
[0155]
[0156] Table 4
[0157] Example 7: Nonporous Hybrid Coating on Pyrrolidone Primed Core
[0158] In this example, an exemplary primed (primed with pyrrolidone) nonporous core with a hybrid coating was fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core with a hybrid coating of the composite particles of the present technology.
[0159] A 5L round bottom flask reactor equipped with a mechanical stirring device, condenser, reactor and thermocouple was set up in an ultrasonic bath capable of heating (490 watts). 14.0 grams of pyrrolidone primed cores (Sample 5A) were redispersed in 112.0 grams of 200 proof ethanol and then loaded into the reactor. 112.0 grams of toluene, 2.7 grams of Pluronic F127 and 7.7 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The ultrasonic bath temperature was raised to 35°C for ultrasonic treatment. The ultrasonic treatment was maintained throughout the coating process. When the ultrasonic bath temperature reached 35°C, a solution containing 9.8 grams of tetraethyl orthosilicate (TEOS), 4.2 grams of 1,2-bis(triethoxysilyl)ethane (BTEE), 0.4 grams of Pluronic F127 in a mixed solvent of 7.0 grams of ethanol (200 proof) and 7.0 grams of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was kept at 35°C for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was dried in a vacuum oven at 70°C overnight. 16.0 g of non-porous BEH coated particles were obtained.
[0160] Example 8: Fabrication of nonporous materials on nonporous hybrid coated cores
[0161] In this example, a nonporous core with a nonporous hybrid coating was fabricated.Other methods and other materials can be utilized to fabricate the primed nonporous polymer core with a nonporous coating of the composite particles of the present technology.
[0162] In a 1L round-bottom flask equipped with a mechanical stirring device, a condenser and a thermocouple, 5.0 grams of nonporous hybrid coated cores (Example 6F, 1.91 μm) were dispersed in 383.3 grams of ethanol and 188.5 grams of water with 11.0 grams of Pluronic P123. The temperature of the reaction slurry was raised to 46°C and the stirring speed was adjusted to 150 RPM. Subsequently, two emulsions were prepared. Emulsion A contained 14.03 grams of tetraethyl orthosilicate (TEOS) and 5.97 grams of 1,2-bis(triethoxysilyl)ethane (BTEE), which were emulsified in a mixed solvent of 36.9 grams of ethanol and 62.8 grams of water with 2.57 grams of Pluronic P123. Emulsion B contained 21.3 grams of N,N-dimethylhexadecylamine, which was emulsified in a mixed solvent of 59.4 grams of ethanol and 29.2 grams of water with 1.74 grams of Pluronic P123. Emulsion A and emulsion B are metered in separately at a constant flow rate over 6 hours via two pumps, and the two streams are combined before flowing into the reactor. The reaction is maintained at 46° C. for 24 hours. After the reaction, the particles are separated by filtration and washed three times with methanol. The particles are further aged for 24 hours at 55° C. in a solution containing 135.0 grams of ethanol, 122.0 grams of water and 30.0 grams of ammonium hydroxide (28% to 30% by weight). After drying overnight in a vacuum oven at 45° C., 9.9 grams of 2.6 μm aged composite particles are obtained. The particles are hydrothermally high-pressure steam treated at 155° C. in a pH 9.8 buffer for 20 hours.
[0163] Example 9: Porous Silica Growth
[0164] In this example, a nonporous core with a porous silica coating was fabricated. Other methods and other materials can be used to fabricate the nonporous polymer core with a nonporous hybrid layer with a porous silica coating of the composite particles of the present technology.
[0165] In a 1L round-bottom flask equipped with a mechanical stirring device, a condenser and a thermocouple, 5.0 grams of non-porous hybrid coated core (Example 6A, 2.05 μm) were dispersed in 306.8 grams of ethanol and 150.8 grams of water with 9.0 grams of Pluronic P123. The temperature of the reaction slurry was raised to 46°C and the stirring speed was adjusted to 150 RPM. A solution was prepared by dissolving 5.7 grams of Pluronic P123 in a binary solvent of 113.6 grams of ethanol and 100.5 grams of water, followed by adding an organic mixture containing 12.1 grams of N,N-dimethylhexadecylamine, 17.54 grams of tetraethyl orthosilicate (TEOS) and 36.0 grams of toluene. The solution was emulsified by ultrasonic treatment and the resulting emulsion was mixed at ambient temperature for 60 minutes. After mixing for 60 minutes, the emulsion was added to the reaction and the reaction was continued at 46°C for 24 hours. After the reaction, the particles were separated by filtration and washed three times with methanol. The particles were further aged at 55°C in a solution containing 135.0 g ethanol, 122.0 g water, and 30.0 g ammonium hydroxide (28 wt % to 30 wt %) for 24 hours. After aging, the particles were subjected to surfactant extraction by sequential treatment in 90 / 10 ethanol / 2N HCl and then refluxing methanol. Next, the dried particles were hydrothermally treated at 100°C in 0.3M pH 5.8 ammonium acetate buffer to increase the pore size. Next, the porous silica shell was prepared for hybrid coating and / or dense bonding by refluxing in 1M HCl for 16 hours, followed by washing with copious water, washing 3 times with acetone, and vacuum drying at 70°C.
[0166] Example 10: Porous Silica Growth and Subsequent Silica Surface Modification
[0167] In this example, a nonporous core with a surface modified porous silica coating (with a nonporous organic-inorganic hybrid material layer) was produced. Other methods and other materials can be used to produce the nonporous polymer core with a surface modified porous silica coating of the composite particles of the present technology.
[0168] In a 10L round-bottom flask equipped with a mechanical stirring device, a condenser and a thermocouple, a 50-gram portion of the nonporous hybrid coated core (Example 6A, 2.05 μm) was dispersed in 3,608 grams of ethanol and 1,508 grams of water with 90 grams of Pluronic P123. The temperature of the reaction slurry was raised to 46°C and the stirring speed was adjusted to 150 RPM. A solution was prepared by dissolving 57 grams of Pluronic P123 in a binary solvent of 1,136 grams of ethanol and 1,005 grams of water, followed by adding an organic mixture containing 121 grams of N,N-dimethylhexadecylamine, 175.4 grams of tetraethyl orthosilicate (TEOS) and 360 grams of toluene. The solution was emulsified by ultrasonic treatment and the resulting emulsion was mixed at ambient temperature for 60 minutes. After mixing for 60 minutes, the emulsion was added to the reaction and the reaction was continued at 46°C for 24 hours. After the reaction, the particles were separated by filtration and washed three times with methanol. The particles were further aged at 55°C in a solution containing 1,350 grams of ethanol, 1,220 grams of water, and 300 grams of ammonium hydroxide (28% to 30% by weight) for 24 hours. After aging, the particles were subjected to surfactant extraction by sequential treatment in 90 / 10 ethanol / 2N HCl and then refluxing methanol. Next, the dried particles were hydrothermally treated at 100°C in 0.3M pH 5.8 ammonium acetate buffer to increase the pore size. Next, the porous silica shell was prepared for hybrid coating and / or dense bonding by refluxing in 1M HCl for 16 hours, followed by washing with large amounts of water, washing 3 times with acetone, and vacuum drying at 70°C. Next, a 10-gram portion of the new polymer core-porous silica particles was further treated by techniques known in the art and previously disclosed to increase the high pH stability of the porous silica coating. The resulting new composite particles have a porous coating suitable for use at high pH and a chromatographically inert composite core that is insoluble at high pH.
[0169] The surfaces of these novel particles can be further modified (eg, with C18, C8, C4, etc.) to produce a bonded phase by techniques well known to those skilled in the art.
[0170] Example 11: Layer-by-layer porous silica growth and subsequent silica surface modification
[0171] In this embodiment, a nonporous core with a surface-modified porous silica coating and a silica layer is manufactured (the core is a polymer center surrounded by an organic-inorganic hybrid material). Other methods and other materials can be used to manufacture a nonporous polymer core with a surface-modified porous silica coating and a silica layer of the composite particles of the present technology.
[0172] 50 grams of non-porous hybrid coated cores (Example 6A, 2.05 μm) were subjected to a layer-by-layer porous silica growth method described in Tanaka and McCalley, Anal. Chem. 2016, 88, 1, 279-298, which is incorporated herein by reference. Standard techniques were used to age, dry, and extract surfactants on the newly made particles. Next, the dried particles were hydrothermally treated at 100 ° C in 0.3M pH 5.8 ammonium acetate buffer to increase the pore size. Next, the porous silica shell was prepared for hybrid coating and / or dense bonding by refluxing in 1M HCl for 16 hours, followed by washing with a large amount of water, washing 3 times with acetone, and drying in vacuo at 70 ° C. Next, 10 grams of these novel polymer core-porous silica particles were further treated by techniques known in the art and previously disclosed to increase the high pH stability of the porous silica coating. The resulting novel composite particles have a porous coating suitable for use at high pH and a chromatographically inert composite core that is insoluble at high pH. Some representative silica coating modification techniques for increasing high pH resistance are listed in the following table (Table 5), which is not intended to be limiting in any way. These methods can be used to modify the silica coating.
[0173]
[0174] Table 5
[0175] The silica coating modification methods of Table 5 are incorporated herein by reference in their entirety and can be used to modify the surfaces of the composite particles disclosed herein.
Claims
1. A composite particle, comprising: a nonporous polymer particle core having a modified surface; a nonporous organic-inorganic hybrid material in contact with the modified surface; and A porous inorganic material is in contact with the nonporous organic-inorganic hybrid material.
2. The particle of claim 1, wherein the non-porous polymer particle core is made from a free radical polymerizable monomer.
3. The particle of claim 2, wherein the nonporous polymer particle core is made of styrene, divinylbenzene, methacrylate or acrylonitrile.
4. The particle of claim 1, wherein the nonporous polymer particle core is made from one or more monomers containing at least two functional groups.
5. The particle of claim 2, wherein the non-porous polymer particle is made from monomers by condensation.
6. The particle of claim 5, wherein the monomer is a carboxylic acid / alcohol or a carboxylic acid / amine.
7. The particle of claim 1, wherein the nonporous polymer particle core is made from one or more monomers capable of being polymerized by ring-opening polymerization.
8. The particle of claim 7, wherein the monomer is an epoxide.
9. The particle of claim 1, wherein at least a portion of the modified surface of the nonporous polymer particle core comprises at least functional groups covalently bonded to a nonporous organic-inorganic hybrid coating to form a functionalized surface.
10. The particle of claim 9, wherein the functional group is at least one of an organosilane characterized by a C-Si, an organotitanium characterized by a C-Ti, and an organozirconium characterized by a C-Zr bond.
11. The particle of claim 1 , wherein at least a portion of the modified surface of the nonporous polymer particle core comprises at least functional groups that electrostatically interact with the nonporous organic-inorganic hybrid coating to form a functionalized surface.
12. The particle of claim 11, wherein the functional group is an amide.
13. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material has a thickness in a range from about 10 nm to about 200 nm.
14. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material has a thickness in a range of about 25 nm to about 100 nm.
15. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material has a pore volume of less than 0.1 cc / g.
16. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material comprises at least one of silica, alumina, titanium, cerium, zirconium, zirconia, or a ceramic material.
17. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material comprises a silicon-based organic-inorganic hybrid material.
18. A composite particle, comprising: a nonporous polymer particle core having a modified surface; a nonporous organic-inorganic hybrid material in contact with the modified surface; a porous inorganic material in contact with the nonporous organic-inorganic hybrid material; and A bonding material is in contact with the nonporous organic-inorganic hybrid material.
19. The particle of claim 18, wherein the binder material is incorporated within the non-porous organic-inorganic hybrid material.
20. The particle of claim 19, wherein the binder material is also deposited on an outer surface of the composite particle.
21. The particle of claim 18, wherein the binding material is also in contact with the modified surface.
22. The particle of claim 21, wherein the binding material is incorporated into the modified surface, deposited on the modified surface, or a combination thereof.
23. A composite particle, comprising: a nonporous polymer particle core having a modified surface; A nonporous organic-inorganic hybrid material is in contact with the modified surface, and the nonporous organic-inorganic hybrid material is deposited on the outermost surface of the porous inorganic material to form a nonporous organic-inorganic hybrid barrier layer on the porous inorganic material outside the composite particle.
24. The composite particle of claim 23, further comprising a binder material.
25. The composite particle of claim 24, wherein the binding material is in contact with at least a portion of the nonporous organic-inorganic hybrid material.
26. The composite particle of claim 23, further comprising a binding material in contact with the nonporous organic-inorganic hybrid barrier layer.
27. The composite particle of claim 23, wherein the nonporous polymer particle core is made of styrene, divinyl benzene, methacrylate, or acrylonitrile.
28. The composite particle of claim 27, wherein the modified surface is a silyl-modified surface.
29. The composite particle of claim 23, wherein the porous inorganic material comprises silica.
30. The composite particle of claim 23, wherein the nonporous organic-inorganic hybrid material comprises a silicon-based organic-inorganic hybrid material.
Citation Information
Patent Citations
Polymer particles with a gradient composition and methods of production thereof
US20190322783A1
Preparation of organically modified silicon dioxides
US4017528A
Porous hybrid particles with organic groups removed from the surface
US6528167B2
Porous inorganic / organic hybrid particles for chromatographic separations and process for their preparation
US6686035B2
Porous hybrid particles with organic groups removed from the surface
US7175913B2